A study on customers satisfaction towards services provided by Kota Kinabalu City Hall (KKCH) / Erma Hastuty Ag Ali - Ag Ali, Erma Hastuty (2006)
This is a study on customer's satisfactions towards services provided by Kota Kinabalu City Hall (KKCH). It is carried out to fulfill the requirement of the Bachelor in Business Administration (Hons) Marketing, final paper. The research tries to provide an in-depth analysis on the customer's satisfactions towards services provided by Kota Kinabalu City Hall and also customer's feedback on Kota Kinabalu City Hall Services. Prior to writing this paper, a survey was conducted by observation with Kota Kinabalu City Hall staffs within the department and as well as customers also were carried out. Apart from that, questionnaires were distributed to the public. The main issues in this research is to find out either the customers satisfy with Kota Kinabalu City Hall services and at the same time to find feedback from customers an actual fulfill their need and wants. The findings of the survey clearly shows that the services still not fulfilled customers need and want. For this research actually, its important to the Kota Kinabalu City Hall itself to achieve customers full satisfaction. City Hall has to increase their labor work in order to fulfilled customers satisfaction or plan the proper strategy of implementation to achieve target and goals.